SARS-CoV-2 dual infection with Delta and Omicron variants in an immunocompetent host: a case report. (November 2022) - Abroi, Aare; Gerst Talas, Ulvi; Pauskar, Merit; Shablinskaja, Arina; Reisberg, Tuuli; Niglas, Heiki; Päll, Taavi; Nelis, Mari; Tagen, Ingrid; Soodla, Pilleriin; Lutsar, Irja; Huik, Kristi
Highlights: Dual infections are rare among patients with respiratory virus infections. An immunocompetent person with dual Delta/Omicron infection was diagnosed. SARS-CoV-2 dual infection is difficult to detect during a single-variant outbreak wave. Abstract: Despite the high number of SARS-CoV-2 infections, only a few cases of dual infection have been reported. Here, we describe a case of COVID-19 caused simultaneously by Delta and Omicron variants in an immunocompetent individual during the early emergence of Omicron variant. A 73-year-old man was hospitalized with suspected acute coronary syndrome and a positive test result for SARS-CoV-2 RNA was received during routine testing at the hospital. He experienced mild symptoms of COVID-19 and was discharged on the ninth day. We sequenced the SARS-CoV-2 whole genome from the sample obtained on admission. The viral sequence was classified as PANGO lineage B.1.1.10 by the Galaxy pipeline; however, on detailed manual analysis, we identified the presence of both Delta and Omicron variants. After excluding the possibilities of a recombinant virus or contamination in the sample, we confirmed the presence of dual infection in this patient. We highlight that dual infections with SARS-CoV-2 may be more common than expected but are difficult to detect during the waves of one dominant variant.